The microplastics effects and possible biological solutions in marine environment: a review - How, Swen Yap; Shukor, Mohd Yunus; Yasid, Nur Adeela (The Malaysian Society for Biochemistry & Molecular Biology, 2021)
The ubiquitous plastic pollutant, occurring as the microplastic (<5 mm) particles in the marine environments. Pristine regions include ocean in Arctic and Antarctica were observed with the presence of marine plastic pollution contributed by few potential transportation routes. The existence of marine plastic pollution poses severe ecotoxicological and ecological risk to the marine organisms and subsequently compromising human population benefits. Hence, this review aims to discuss about marine microplastics, emphasizing their toxic effects to marine organisms and the possible biological approaches to remove marine microplastic. Several combined toxicity effects contributed from the combination of microplastic and chemical additives (i.e., Polybrominated diphenyl ethers, oxybenzone, chlorpyrifos & glyphosate) were also discussed to highlight the actual presence of these pollutants in the marine plastic polluted sites. Recent studies have suggested the plastic biodegradation as a feasible removal approach, thus the potential exploitation of the microorganisms was reviewed in accordance with the marine plastic pollution.